2019
DOI: 10.1002/jbmr.3866
|View full text |Cite
|
Sign up to set email alerts
|

Murine Placental-Fetal Phosphate Dyshomeostasis Caused by an Xpr1 Deficiency Accelerates Placental Calcification and Restricts Fetal Growth in Late Gestation

Abstract: Phosphorus is a necessary component of all living organisms. This nutrient is mainly transported from the maternal blood to the fetus via the placenta, and insufficient phosphorus availability via the placenta disturbs the normal development of the fetus, especially fetal bone formation in late gestation. Key proteins (phosphate transporters and exporters) that are responsible for the maintenance of placental‐fetal phosphorus homeostasis have been identified. A deficiency in the phosphate transporter Pit2 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…31 XPR1 plays an important role in maintaining placental-fetal Pi homeostasis, disruption of which causes severe placental calcification, delays normal placental function, and restricts fetal growth. 32 Mutations in XPR1, a gene encoding an inorganic phosphate exporter, have recently been identified in patients with primary familial brain calcification. 33 XPR1, a previously identified cellular receptor for several murine leukemia viruses, plays a role in many pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…31 XPR1 plays an important role in maintaining placental-fetal Pi homeostasis, disruption of which causes severe placental calcification, delays normal placental function, and restricts fetal growth. 32 Mutations in XPR1, a gene encoding an inorganic phosphate exporter, have recently been identified in patients with primary familial brain calcification. 33 XPR1, a previously identified cellular receptor for several murine leukemia viruses, plays a role in many pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that in zebrafish, xpr1b, an ortholog of XPR1, is crucial for the dif-ferentiation of tissue-resident macrophages and microglia (51). In mice, the full knockout of Xpr1 is embryonic lethal (52), but whether the absence of Xpr1 affects microglia development has not been assessed. Thus, further studies are needed to dissect the role of PFBC genes in microglial function.…”
Section: Discussionmentioning
confidence: 99%
“…This nutrient is mainly transported from the maternal blood to the fetus via the placenta. Xu et al [44] found that XPR1 was highly expressed in the murine placenta, but the placenta of the murine that knocks out this gene was severely calcified. Soluble carrier family 7 member 11 (SLC7A11) gene is a target of p53-mediated transcriptional repression, and p53 can inhibit the uptake of cystine by repressing the expression of SLC7A11.…”
Section: Differential Expression Analysis and Functional Analysis Of Circrnasmentioning
confidence: 99%